EDUCATION AS A FOUNDATION OF NATIONAL DEVELOPMENT: POLICY ANALYSIS AND ITS IMPLICATIONS IN INDONESIA - Mokhamad Yaurizqika Hadi (International Conference on Humanity Education and Society (ICHES), 2025)
Education has a strategic role as the main foundation of national development,because it contributes directly to improving the quality of human resources (HR) andsupporting sustainable economic, social, and political growth. This study aims toanalyze education policies in Indonesia and evaluate their implications for nationaldevelopment. Using a descriptive qualitative approach with a policy study design, thisstudy utilizes literature studies, policy document analysis, and secondary data fromvarious official sources. The results of the study show that although there is a policycommitment to make education a driver of development, challenges such as inequalityof access, teacher quality, infrastructure, and the digital divide are still majorobstacles. The implementation of policies such as the Independent Curriculum andNational Assessment has also not been optimal in many regions. This study emphasizesthe importance of collaboration between the government, private sector, and civilsociety, as well as the need for holistic and adaptive education reform so that educationtruly functions as a solid foundation for inclusive and sustainable nationaldevelopment.